Connecting the World: The Physical Platform of International Telecommunication - Ola Khaled (International Telecommunications Society (ITS), 2019)
This paper aims to give an overview on a very specific field in telecommunication which is the submarine cables industry. It covers some statistics on the used international bandwidth, historical milestones and information on the submarine cables' construction, geography, ownership evolvement, challenges and their remedies. The paper provides specific information on the international cables geography of key players in the MENA region. Information presented in the paper are a combination of reliable sources of information such as Telegeography and ICPC (reference below), hands on experience and common practices in the international data wholesale and the subsea cables industry. Few may think that satellites are responsible for carrying international traffic, but the cables have proven to offer much larger capacity for far less cost. It is the pipes on the ocean floor that form the backbone of the world's modern economy (source: policyexchange.org.uk). The traffic running on international cables accounts for 99% whether they are terrestrial interborders or laid underwater. The international traffic exchanged globally is not only used for internet traffic, which makes up for 90% but also, 5% for enterprise traffic, 3% for research and education related traffic and 0.01% for voice traffic. These portions may vary from one route to another. As per telegeography, the used international bandwidth globally as by 2017 approaches 700 Tbps with a forecasted CAGR of 45% to reach 10Pbps in 2024. The first successful attempt ever to build a submarine telegraph cable was in 1850. And many more has followed, today there are several hundreds of subsea cables in service globally. Almost most coastal countries are connected to submarine cable systems. (...)
Keywords: 330